Endoscopic resection versus surgery for early gastric cancer: a systematic review and meta‐analysis. Issue 5 (2nd March 2016) - Sun, Kaiyu; Chen, Shuling; Ye, Jinning; Wu, Hui; Peng, Jianjun; He, Yulong; Xu, Jianbo
Abstract : Objectives: Endoscopic resection (ER) is becoming an increasingly used treatment option for early gastric cancer (EGC); however, data comparing the long‐term outcomes of ER and surgery are limited. Accordingly, we here aimed to perform a meta‐analysis to clarify the long‐term outcomes and safety of ER and surgery for EGC. Methods: Literature on the direct comparison of ER and surgery for EGC was retrieved from the Medline, PubMed and Scopus databases. We selected the eligible studies, extracted data, and assessed the quality scores according to the guidelines. The overall survival (OS), recurrence‐free survival (RFS), and adverse event rates were investigated, and the pooled hazard ratio (HR), odds ratio (OR), and 95% confidence interval (CI) were estimated. Results: Nine retrospective studies were identified, including 973 and 1190 participants undergoing ER and surgery, respectively. There were no significant differences regarding the OS (HR: 0.995, 95% CI: 0.836‐1.185; P = 0.959) and adverse event rates (OR: 0.50, 95% CI: 0.20‐1.28, P = 0.148) between ER and gastrectomy. However, patients undergoing ER had significantly shorter RFS (HR: 7.226, 95% CI: 1.718‐30.400, P = 0.007) than those undergoing gastrectomy. Conclusions: Despite the limitations of this review, including the retrospective nature of all included studies, our results suggest that ER might be a feasible and safe treatment strategy compared to that of gastrectomy for EGC; however, careful endoscopic surveillance is needed for ensuring favorable outcomes. These findings should be confirmed in further large‐scale, prospective, randomized, controlled trials from different countries.